Next-Generation Beneficial Microbes: The Case of Akkermansia muciniphila - Cani, Patrice D.; de Vos, Willem M. (Frontiers in Microbiology, 2017)
Metabolic disorders associated with obesity and cardiometabolic disorders are worldwide epidemic. Among the different environmental factors, the gut microbiota is now considered as a key player interfering with energy metabolism and host susceptibility to several non-communicable diseases. Among the next- generation beneficial microbes that have been identified, Akkermansia muciniphila is a promising candidate. Indeed, A. muciniphila is inversely associated with obesity, diabetes, cardiometabolic diseases and low-grade inflammation. Besides the numerous correlations observed, a large body of evidence has demonstrated the causal beneficial impact of this bacterium in a variety of preclinical models. Translating these exciting observations to human would be the next logic step and it now appears that several obstacles that would prevent the use of A.muciniphila administration in humans have been overcome. Moreover, several lines of evidence indicate that pasteurization of A. muciniphila not only increases its stability but more importantly increases its efficacy. This strongly positions A. muciniphila in the forefront of next- generation candidates for developing novel food or pharma supplements with beneficial effects. Finally, a specific protein present on the outer membrane of A. muciniphila, termed Amuc_1100, could be strong candidate for future drug development. In conclusion, as plants and its related knowledge, known as pharmacognosy, have been the source for designing drugs over the last century, we propose that microbes and microbiomegnosy, or knowledge of our gut microbiome, can become a novel source of future therapies.